Transdiagnostic cognitive-behavioral therapy for patients with eating disorders: a two-site trial with 60-week follow-up. - Fairburn, C; Cooper, Z; Doll, H; O'Connor, M; Bohn, K; Hawker, D; Wales, J; Palmer, R (2009)
OBJECTIVE: The aim of this study was to compare two cognitive-behavioral treatments for outpatients with eating disorders, one focusing solely on eating disorder features and the other a more complex treatment that also addresses mood intolerance, clinical perfectionism, low self-esteem, or interpersonal difficulties. METHOD: A total of 154 patients who had a DSM-IV eating disorder but were not markedly underweight (body mass index over 17.5), were enrolled in a two-site randomized controlled trial involving 20 weeks of treatment and a 60-week closed period of follow-up. The control condition was an 8-week waiting list period preceding treatment. Outcomes were measured by independent assessors who were blind to treatment condition. RESULTS: Patients in the waiting list control condition exhibited little change in symptom severity, whereas those in the two treatment conditions exhibited substantial and equivalent change, which was well maintained during follow-up. At the 60-week follow-up assessment, 51.3% of the sample had a level of eating disorder features less than one standard deviation above the community mean. Treatment outcome did not depend on eating disorder diagnosis. Patients with marked mood intolerance, clinical perfectionism, low self-esteem, or interpersonal difficulties appeared to respond better to the more complex treatment, with the reverse pattern evident among the remaining patients. CONCLUSIONS: These two transdiagnostic treatments appear to be suitable for the majority of outpatients with an eating disorder. The simpler treatment may best be viewed as the default version, with the more complex treatment reserved for patients with marked additional psychopathology of the type targeted by the treatment.